1998
DOI: 10.1200/jco.1998.16.8.2817
|View full text |Cite
|
Sign up to set email alerts
|

Transplant-lite: induction of graft-versus-malignancy using fludarabine-based nonablative chemotherapy and allogeneic blood progenitor-cell transplantation as treatment for lymphoid malignancies.

Abstract: These findings indicate the feasibility of allogeneic hematopoietic transplantation with a nonablative preparative regimen to produce engraftment and GVL against lymphoid malignancies. The ability to induce remissions with donor lymphocyte infusion in patients with CLL, Richter's, and low-grade and intermediate-grade lymphoma is direct evidence of GVL activity against these diseases. This approach appears to be most promising in patients with chemotherapy-responsive disease and low tumor burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
496
1
9

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 857 publications
(520 citation statements)
references
References 32 publications
14
496
1
9
Order By: Relevance
“…To overcome this obstacle, allogeneic HSCT with a reduced-intensity (RIST) or nonmyeloablative conditioning regimen has recently been explored for patients who are ineligible to receive conventional myeloablative HSCT (CIST) due to age limits or comorbidities. Many studies suggested that RIST is a reasonable option for older patients or patients with comobidities with acceptable treatment-related complications or morbidity, while preserving adequate antitumor effects [1][2][3][4][5][6][7][8][9][10][11][12]. However, these studies mostly pursued different variables including disease types, stages [1,4-6, 8,12], donor type [1,2,5,10], graft source [1,2], conditioning regimens [4,5,7,9], and/or GvHD prophylaxis [1,4,9].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this obstacle, allogeneic HSCT with a reduced-intensity (RIST) or nonmyeloablative conditioning regimen has recently been explored for patients who are ineligible to receive conventional myeloablative HSCT (CIST) due to age limits or comorbidities. Many studies suggested that RIST is a reasonable option for older patients or patients with comobidities with acceptable treatment-related complications or morbidity, while preserving adequate antitumor effects [1][2][3][4][5][6][7][8][9][10][11][12]. However, these studies mostly pursued different variables including disease types, stages [1,4-6, 8,12], donor type [1,2,5,10], graft source [1,2], conditioning regimens [4,5,7,9], and/or GvHD prophylaxis [1,4,9].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to extend the use of allogeneic HCT to older patients and those with comorbid conditions, several groups of investigators have explored allogeneic HCT after reduced-intensity [8][9][10] or truly nonmyeloablative conditioning regimens [11][12][13][14] in which the burden of tumour eradication was shifted toward GVT effects.…”
Section: Centermentioning
confidence: 99%
“…Furthermore, recently, non-myeloablative drug combinations as a regimen for allogeneic hematopoietic stem cell transplantation have been used extensively to reduce regimen related toxicity, including cardiotoxicity [36][37][38]. Nishio et al reported successful nonmyeloablative stem cell transplantation in a case with severe aplastic anemia complicated by heart failure [39].…”
Section: Discussionmentioning
confidence: 99%